AdubaPE - application low code to assist farmers in soil fertilization and correction in Pernambuco - de Melo Telles, Paulo Victor (2023)
Information and communication technology has been gaining more and more space in the management of city and rural problems, bringing efficiency, agility in processes and improving results and people's quality of life. Access to applications, social networks, and IoT (Internet of Things) devices has been intensifying and becoming increasingly popular, enabling the inclusion of more people in the digital world. The objective of this work was to develop a low code application that allows farmers, based on analytical reports of the soil, to verify the recommendation of fertilization and liming necessary for the crop to be planted. The technical data on fertilization and liming for the various crops planted in the state were obtained from the tables of recommendations for fertilizers and soil amendments for the state of Pernambuco, as Brazil, due to its large territorial dimension, has different types of soils, as well as predominant types of crops by region. The low code tool used was kodular, developed in MIT App Inventor to facilitate the coding of applications. This product is expected to provide opportunities for farmers in the state to minimize costs and increase productivity, as well as help protect the environment, since the exaggerated supply of fertilizers and soil amendments can lead to contamination, as well as surface and underground water with damage to the main uses. It is expected that food production aligned with sustainable innovation can contribute to improving the quality of life for people and the environment.